Survie, révolte et luttes queers agressives : textes du Street Transvestite Action Revolutionaries - Rivera, Sylvia; Certaines d'Entre Nous; Johnson, Marsha P.; Nothing, Ehn (Certaines d'Entre Nous)
Fonds Suzan Daniel (FSD)
Frans
Brochure